(untitled) (Journal of the College of Education for Women, 2019)
SummaryThe subject ( meaning of added verbs) is one of the main subjectswhich study in morphology since in Arabic language. It is include the meaningof each format, and the increased meaning occurred by this increment in theverbs.The (strain) is one of very important meaning in this subject, it takes awide area of morphology studies, and interesting of scientists andresearchists.There are two famous formats for this meaning; (infa la انفعل ), and (iftala افتعل ). Also There are another formats for the same meaning, but less thanthe first two in use, they are; (taf ala تفعّل ), (tafa ala تفاعل ), (taf lala ) ,(تفعللifanlala افعنلل ), (ifanla .(افعنلىThe hypotheses of this reaserch say: That the kind of strain in theformats which contain in them structures a voice of (al noon) deferent from thekind of strain in the format when it contains a voice of (al ta a).The search proved this hypothesis, so the result was refer to followingfact:The first kind of strain which occurred from the first group of addedverbs refers to duality nature, or it refers to the short time of action happening,while the second kind of strain, no one can expect it is naturality before actionhappening.